2020
DOI: 10.33094/7.2017.2020.62.78.87
|View full text |Cite
|
Sign up to set email alerts
|

Accounting Students, Social Media and Online Learning in West Africa’s Topmost University

Abstract: All over the world, accounting students have the burden of scholarship and professional studies in order to become future accountants. A way to cope with this demand is to use the ubiquitous social media. This study examined the demographic differentials in the students' awareness and usage of social media as online pedagogical tools. Purposely selected for the study were accounting students of Covenant University, ranked number one in West Africa by the 2019 Times Higher Education. The university enrols its a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The media used for online learning is increasingly popular and diverse, creating virtual classrooms in cyberspace such as Google Classroom, Class-in, Edmodo, and WhatsApp. Other platforms help people interact with each other through live video, such as Zoom, Google Meeting, Microsoft Teams, and others (Kind & Evans, 2015;Moşteanu, 2021;Odiboh et al, 2020). In addition to the main function of helping students maintain their learning and improve their understanding, each platform is supplied by different publishers, so they offer different functions.…”
Section: Online Learning Mediamentioning
confidence: 99%
“…The media used for online learning is increasingly popular and diverse, creating virtual classrooms in cyberspace such as Google Classroom, Class-in, Edmodo, and WhatsApp. Other platforms help people interact with each other through live video, such as Zoom, Google Meeting, Microsoft Teams, and others (Kind & Evans, 2015;Moşteanu, 2021;Odiboh et al, 2020). In addition to the main function of helping students maintain their learning and improve their understanding, each platform is supplied by different publishers, so they offer different functions.…”
Section: Online Learning Mediamentioning
confidence: 99%
“…In the scientific literature, the term social adjustment is often used as a synonym of socio-psychological adaptation. Social adjustment is understood as a psychological process that includes coping with new social standards and values for individual acceptance [28,29].…”
Section: The Study Of Types Of Adaptationmentioning
confidence: 99%
“…Considerable research has found that technology platforms significantly facilitate learning and support students' achievement and performance (e.g., (Babaali & Gonzalez, 2015;Cai, Liu, Wang, Liu, & Liang, 2021;Odiboh et al, 2020;Roschelle, Feng, Murphy, & Mason, 2016;Siegle, Amspaugh, & Mitchell, 2017;Verma, Stoffova, & Zoltán, 2018)). Recently researchers in the field of education have concentrated more on the effectiveness of designing educational applications that align with students' interests, which may help educators to integrate these applications, especially social media platforms into their curricula.…”
Section: Introductionmentioning
confidence: 99%